Rancang Bangun Aplikasi Buku Kas berbasis Website dengan metode Extreme Programming - BRYAN ADE BANDASO; CANDRA TAUFIK KUSTIYONO; WIDI SETIAWAN; OKTAVIA ZULFANTI; AFIF DWI LAKSONO (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
Cash book is a book that records all receipts and payments. Beginning balances, receipts, disbursements and cash balances at the end of a certain period are all recorded in the general cash book. If only manual recording is done, the filing system and materials that cannot be used will be stored in the archive. Technology makes a computerized data management system so that data can be managed quickly and accurately. In managing the budget there are still many agencies that use conventional systems. With this website, it is expected that users can report every day and can record reports automatically through the online system so that they can be accessed anywhere and anytime. In this study, the extreme programming method was used as a method for creating a financial recording information system and conducting blackbox testing with 100% successful results.